Missiology in the Digital Wave: Reflections of Church Leaders on Ministry and Evangelism at Gereja GMIM Victory Minanga Indah - Arkyanne Paulina Haniko; Joan Elisa Hamel; Naftali Angelica Pangalila Koemesan (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2024)
This article discusses how churches are adapting their missiology in the digital age by combining traditional methods and modern technology to reach younger generations. Through a mixed-method approach and interviews with leaders of the GMIM Victory Minanga Indah church, the study found that technological advances have opened up significant opportunities for spreading the Gospel through social media and digital platforms. However, the main challenge is maintaining the depth and authenticity of the Gospel message amid the rapid and diverse flow of information. Therefore, ministry strategies must be innovative, contextual, and interactive to be more effective and relevant. The role of church leaders is crucial in managing technology while upholding theological values to ensure the mission remains rooted in Christian teachings. In conclusion, missiology in the digital age must be dynamic and adaptive, blending technology with the foundation of faith to expand the reach of ministry in an inclusive and sustainable manner.